A prospective, molecular epidemiology study of EGFR mutations in Asian patients with advanced non-small-cell lung cancer of adenocarcinoma histology (PIONEER) - Yuankai Shi (2018)
INTRODUCTION:: PIONEER (NCT01185314) was a prospective, multinational, epidemiological study of epidermal growth factor receptor (EGFR) mutations in patients from Asia with newly diagnosed advanced lung adenocarcinoma. METHODS:: Eligible patients (aged ≥20 years) had untreated stage IIIB/IV adenocarcinoma. The EGFR mutation status (primary end point: positive, negative, or undetermined) of tumor samples (biopsy, surgical specimen, or cytology) was determined (Scorpion amplification refractory mutation system). EGFR mutation frequency was calculated and compared between demographic and clinical subgroups. RESULTS:: Of 1482 patients from seven Asian regions, 43.4% of patients were female, median age was 60 years (range, 17-94), and 52.6% of patients were never-smokers. EGFR mutation status was evaluable in tumors from 1450 patients (97.8%) (746 [51.4%] positive; 704 [48.6%] negative). Country, sex, ethnicity, smoking status, pack-years (all p < 0.001), disease stage (p = 0.009), and histology type (p = 0.016) correlated significantly with EGFR mutation frequency. Mutation frequency was 61.1% in females, 44.0% in males; lower in patients from India (22.2%) compared with other areas (47.2%-64.2%); highest among never-smokers (60.7%); and decreased as pack-year number increased (>0-10 pack-years, 57.9%; >50 pack-years, 31.4%) (similar trend by sex). Ethnic group (p < 0.001) and pack-years (p < 0.001) had statistically significant associations with mutation frequency (multivariate analysis); sex was not significant when adjusted for smoking status. CONCLUSION:: PIONEER is the first prospective study to confirm high EGFR mutation frequency (51.4% overall) in tumors from Asian patients with adenocarcinoma. The observed high mutation frequency in demographic/clinical subgroups compared with white populations suggests that mutation testing should be considered for all patients with stage IIIB/IV adenocarcinoma, even males and regular smokers, among Asian populations. © 2013 by the International Association for the Study of Lung Cancer.